The beta Subunit of Nascent Polypeptide Associated Complex Plays A Role in Flowers and Siliques Development of Arabidopsis thaliana - Fíla, Jan; Klodová, Božena; Potěšil, David; Juříček, Miloslav; Šesták, Petr; Zdráhal, Zbyněk; Honys, David (International journal of molecular sciences, 2020)
The nascent polypeptide-associated (NAC) complex was described in yeast as a heterodimer composed of two subunits, α and β, and was shown to bind to the nascent polypeptides newly emerging from the ribosomes. NAC function was widely described in yeast and several information are also available about its role in plants. The knock down of individual NAC subunit(s) led usually to a higher sensitivity to stress. In Arabidopsis thaliana genome, there are five genes encoding NACα subunit, and two genes encoding NACβ. Double homozygous mutant in both genes coding for NACβ was acquired, which showed a delayed development compared to the wild type, had abnormal number of flower organs, shorter siliques and greatly reduced seed set. Both NACβ genes were characterized in more detail-the phenotype of the double homozygous mutant was complemented by a functional NACβ copy. Then, both NACβ genes were localized to nuclei and cytoplasm and their promoters were active in many organs (leaves, cauline leaves, flowers, pollen grains, and siliques together with seeds). Since flowers were the most affected organs by nacβ mutation, the flower buds' transcriptome was identified by RNA sequencing, and their proteome by gel-free approach. The differential expression analyses of transcriptomic and proteomic datasets suggest the involvement of NACβ subunits in stress responses, male gametophyte development, and photosynthesis.
Keywords: proteiny huseníčku; semena rostlinná; transkriptom; molekulární chaperony; fenotyp; Phenotype; homozygot; mutace; Arabidopsis; klíčení; Plant Development; Transcriptome; Molecular Chaperones; Arabidopsis Proteins; Germination; květy; Homozygote; Seeds; Arabidopsis thaliana, chaperone, flower bud proteome, flower bud transcriptome, male gametophyte, nascent polypeptide-associated complex; regulace genové exprese u rostlin; proteomika; Plants, Genetically Modified; Flowers; Gene Expression Regulation, Plant; geneticky modifikované rostliny; Mutation; Alleles; Proteomics; vývoj rostlin; alely